Insulin‐like growth factor‐1 and site‐specific cancers: A Mendelian randomization study. (27th July 2020) - Larsson, Susanna C.; Carter, Paul; Vithayathil, Mathew; Kar, Siddhartha; Mason, Amy M.; Burgess, Stephen
Abstract: Insulin‐like growth factor‐1 (IGF‐1) is involved in several processes relevant to carcinogenesis. We used 416 single‐nucleotide polymorphisms robustly associated with serum IGF‐1 levels to assess the potential causal associations between this hormone and site‐specific cancers through Mendelian randomization. Summary‐level genetic association estimates for prostate, breast, ovarian, and lung cancer were obtained from large‐scale consortia including individuals of European‐descent. Furthermore, we estimated genetic associations with 14 site‐specific cancers in European‐descent individuals in UK Biobank. Supplementary analyses were conducted for six site‐specific cancers using summary‐level data from the BioBank Japan Project. Genetically predicted serum IGF‐1 levels were associated with colorectal cancer. The odds ratio (OR) per standard deviation increase of IGF‐1 levels was 1.11 (95% confidence interval [CI] 1.01‐1.22; P  = .03) in UK Biobank and 1.22 (95% CI 1.09‐1.36; P  = 3.9 × 10 −4 ) in the BioBank Japan Project. For prostate cancer, the corresponding OR was 1.10 (95% CI 1.01‐1.21; P  = .04) in UK Biobank, 1.03 (95% CI 0.97‐1.09; P  = .41) in the prostate cancer consortium, and 1.08 (95% CI 0.95‐1.22; P  = .24) in the BioBank Japan Project. For breast cancer, the corresponding OR was 0.99 (95% CI 0.92‐1.07; P  = .85) in UK Biobank and 1.08 (95% CI 1.02‐1.13; P  = 4.4 × 10 −3 ) in the Breast Cancer Association Consortium. There was no statistically significant association between genetically predicted IGF‐1 levels and 14 other cancers. This study found some support for a causal association between elevated serum IGF‐1 levels and increased risk of colorectal cancer. There was inconclusive or no evidence of a causal association of IGF‐1 levels with prostate, breast, and other cancers. Abstract : This Mendelian randomization study found support for a causal association between elevated serum insulin‐like growth factor‐1 levels and increased risk of colorectal cancer.